The Lexical Density and Experiential Structure of Nominal Groups of the Discussion Section of Skripsis and Research Articles - Sudrajat, Muhamad Wisam; wachidah, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2022)
This research aimed to see the lexical density of the discussion section of three skripsis (SK) and three research articles (RA) and the experiential structure of its nominal groups. Halliday’s lexical density measurement, which divides the number of lexical items by the number of clauses, was used. It was found that SK has a higher lexical density level than RA (8,5 compared to 6,8). The reason is that one of the SK texts repeats dozens of lexical items in one clause, giving it a high lexical density score. If the text were to be ignored, then SK’s lexical density would be lower than RA (5,7 compared to 6,8). SK was found to have fewer nominal groups than RA (236 compared to 255). RA uses classifier and qualifier, which are realized by lexical items, more than SK, while SK leads in numerative, which is often realized by function words. It is concluded that SK, which has lower lexical density, also uses a more ‘simple nominal group structure’ i.e only having one premodifier or postmodifier, and utilizes lexical items in their nominal groups less frequently than RA did.